ANALISIS PENGARUH LIKUIDITAS TERHADAP MISPRICING PADA SAHAM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2013 - F. A. Minori Christine Waruwu; Wahyu Ario Pratomo (Departemen Ekonomi Pembangunan USU, 2015)
This research aims to test and analyze the effect of stock liquidity on stock mispricing which listed at Indonesia Stock Exchange. The applied sampling method is purposive sampling. The sample in this research is banking firms registered during January 2010 up to December 2013.The analysis method applied to analyze the influence stock liquidity on stock mispricing is descriptive analysis. Stock liquidity uses three measure: amihud illiquidity, amihud risk and share turnover. This research uses multiple regression and panel data with 22 banking companies listed which based on criteria of research at Indonesia Stock Exchange as a sample. The result of this research shows during Januari 2010 – December 2013 that size and book to market ratio have negative effects and not significantly influence on banking’s stock mispricing in Indonesia. Stock liquidity measured by amihud illiquidity shows that liquidity has positive and significantly influence banking’s stock mispricing in Indonesia. Stock liquidity measured by amihud risk shows that liquidity has negative and not significantly influence banking’s stock mispricing in Indonesia. Stock liquidity measured by amihud share turnover shows that liquidity has positive and significantly influence banking’s stock mispricing in Indonesia.Keyword: mispricing, size, book to market ratio, liquidity